Sirtuin 1 (SIRT1) and activated caspase 3 expression on rat spinal cord in acute phase after Sciatic nerve injury (Bangladesh Journal of Medical Science, 2018)
Background: Increase of SIRT1 expression inhibit the increase of activated Caspase 3 expression in acute phase of traumatic brain injury (TBI). However, the SIRT1 expression on rat spinal cord in acute phase after peripheral nerve injury was unknown.Objective: To reveal SIRT1and activated Caspase 3 expression on rat spinal cord in acute phase after sciatic nerve injury and to reveal the correlation between SIRT1 and activated Caspase 3 expression after sciatic nerve injury.Method: Thirty male Wistar rats aged 3 months were divided into sham operated and crush injury group. Termination was performing at days 3, 7 and 14. Lumbar spinal cord segments 4-5 (VTh12-VL1 high) embedded in paraffin blocks. Imunohistochemistry staining was performed using antibody of SIRT1 nuclear marker and activated Caspase 3. Observations were performed by two double blinded observers in 400x magnification. The data were analyzed using unpaired t-test and Pearson correlation. All data were processed using statistical analysis with confidence interval (CI) 95% and limit of significance (p-values)